Biodegradable polyester-based hyperbranched nanocarrier-modified with N-acetyl glucosamine for efficient drug delivery to cancer cells through GLUTs - Shaikh, Aazam; Salve, Rajesh; Sengar, Devyani; Gajbhiye, Virendra (Frontiers in Bioengineering and Biotechnology, 2025)
Cancer, ranking just below cardiovascular diseases, is a leading cause of mortality worldwide. The key to enhancing survival rates among cancer patients lies in the early detection, removal, and treatment of tumors. However, the broad-spectrum nature of current treatments, including chemotherapy and radiation therapy, results in significant collateral damage to healthy cells and tissues. In this context, hyperbranched polymers present a promising avenue for more targeted therapy. These polymers can be loaded with chemotherapeutic drugs and modified with specific ligands to selectively target cancer cells via glucose transporters, which are overexpressed in many cancer types. To enhance the delivery of drugs to cancer cells, we have engineered an N-acetyl glucosamine conjugated version of this polymer. The characterization of these nanocarriers was evaluated using various techniques, including 1H NMR, dynamic light scattering, and FTIR spectroscopy. Additionally, confocal microscopy was utilized to compare the accumulation of doxorubicin in cancer cells using both the N-acetyl glucosamine-conjugated and unmodified versions of H40 Boltorn™. Our observations indicated a superior accumulation of doxorubicin in cells treated with the modified H40 polymer. Further evaluation of the drug-loaded nanocarriers was conducted on MDA-MB-231 and 4T1 breast cancer cell lines, focusing on their cytotoxic effects. This suggests that the targeted delivery of anticancer drugs using the modified H40 Boltorn™ nanocarriers significantly enhances the ability to kill breast cancer cells, offering a more efficient and selective approach to chemotherapy that minimizes impact on healthy tissues and cells.